BIODIESEL DARI MINYAK JELANTAH MENGGUNAKAN KATALIS BASA HETEROGEN BERBAHAN DASAR ABU TANDAN KOSONG KELAPA SAWIT (ATKKS) - Duafrizal Joycorleon Manik; Faizah Hamzah; Fajar Restuhadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Currently Indonesia is still heavily dependent on fossil fuels as an energy source. To reduce dependence on oil and meet global enviromental requirements, one way is with the development of enviromentally friendly fuel that is and alternative energy derived from plant oil called biodiesel. This study uses a Completely Randomized Design (CRD) with five treatments, S1 (Reaction transesterification 1 hour), S2 (transesterification 2 hours), S3 (transesterification 3 hours), S4 (transesterification 4 hours), and S5 (transesterification 5 hours) with three replications. The data were analyzed using ANOVA, continued by DNMRT at 5 % level. The results showed that the transesterification reaction time significantly (P<0.05) viscosity, water content, levels of methyl ester. But did not significantly affect (P>0.05) on influenced the acid number, total glycerol, flash point, saponfication. The analysis has been carried obtained the best treatment is S5 with the results said saponfication (103.52 mg KOH/g), the acid value (1.29 mg KOH/g), total glycerol (0.19 %), viscosity (2.21 cSt), water content (0.02 %), flash point (115°C ), and the level of methyl ester (99.32 %). Keywords: biodiesel, waste cooking oil, catalyst transesterification reaction.